Schooling the boys : masculinities and primary education - Skelton, Christine (Open University Press, 2001)
"This title explores where masculinity is in primary schools. It has been argued by some commentators that a contributory factor to boys' underachievement is the predominance of women teachers in primary schools which has led to classroom management and teaching styles which "favour" girls. As this book shows, primary schools produce a range of masculinities for pupils to draw on. A number of questions are raised: what are the tensions for boys between what the school expects from them as "school pupils" and how they are drawn to behave as a "boy"? How does a primary school produce certain masculine styles in its day-to-day routines? In what ways do girls respond to male practices and behaviours in the primary school classroom? The book aims to provide readers with an understanding of the background literature on boys and schooling, an insight into "masculinity-making" in primary schools, and to offer strategies for developing gender-relevant programmes."--BOOK JACKET.